Identifikasi Status Gizi, Faktor Risiko dan Inisiasi Kebiasaan Bawa Bekal Pada Anak TK-Active: Identifikasi Status Gizi, Faktor Risiko dan Inisiasi Kebiasaan Bawa Bekal Pada Anak TK-Active - Liberty, Iche; Septadina, Indri Seta; Kurniati, Ardesy Melizah; Utama, Meria; Ananingsih, Esti Sri (IKesT Muhammadiyah Palembang, 2024)
The main aspect of the challenge related to children's food patterns and intake is the availability of snacks and drinks sold in the school environment with high energy and fat and low fruit and vegetables. This community service aims to increase knowledge related to risks, healthy eating patterns, and the importance of bringing children to school. In addition, nutritional status and identification of eating habits of fruits and vegetables in students were also measured. This activity was carried out on August 19, 2022 with strict implementation of health protocol discipline. The majority of students at TK -Active have normal nutritional status with a total of 53 people (73.61%). Carrot is the students' favorite vegetable with 17 people (37.74%) although most parents (46.67%) like all vegetables. Oranges are the students' favorite fruit with 11 people (24.44%), as well as the parents of most students also like oranges, totaling 15 people (33.33%). There are similarities in food preferences both healthy and unhealthy in parents and their children, especially if they eat together more often. Parents have a big role in determining children's eating preferences.